KEKUATAN NASIONAL TIONGKOK DALAM SENGKETA LAUT TIONGKOK SELATAN - Sukawarsini Djelantik (Indonesian Journal of International Relations, 2021)
The South China Sea (LTS) has a strategic position and rich in natural resources. These waters are claimed by several countries such as China, the Philippines, Vietnam, Malaysia, Brunei Darussalam, and Taiwan. The overlapping claims have not yet reached a resolution, even though tensions have increased and potentially to become an open conflict. The United States (US) and China have economic, political and strategic interests in winning the competition in the South China Sea. This paper answers the question what is China's position in the dispute in the South China Sea? Has China as a great power succeeded in utilizing its national power to control the waters? China's position is analyzed using the concept of national power consisting of Diplomacy, Information, Military and Economics (DIME), which is commonly used to assess state power. China's strength is compared indirectly with the US, which is the main competitor in the region from a diplomatic, military and economic point of view. From the diplomatic aspect, China controls countries in Southeast Asia which are part of the Belt and Road Initiative (BRI) infrastructure project, whose various projects are funded through the Asian Investment Infrastructure Bank (AIIB). To confirm the claim, China has carried out various constructions of artificial islands in the disputed area, which are equipped with military facilities. From an economic perspective, China's rapid growth in recent decades has made it one of the most respected world powers. These facts indicated that China is a great power that has managed to match the power and influence of the US in the region. In the case of the LTS dispute, it is likely that China will win the competition, influence and support from the disputing countries. China; South China Sea; diplomacy, information, military, economy